Peer Collaboration in Enhancing the Success of Junior High School Students' Group Projects - Nabila Vega Rahmawati; Nurizsa Aulya Syifa; Suparmi (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to analyze the effectiveness of the group project learning model as a key strategy to overcome low collaboration and creativity skills in students, which are often caused by the use of conventional learning methods. Through a quantitative approach in the form of classroom action research and descriptive qualitative methods, the results of the study show that the implementation of group projects has a very significant effect on developing collaborative skills as an important competency in the 21st century. Consistent implementation of PjBL has a positive and significant effect on improving students' cooperation, communication, and creativity in completing learning projects. In addition, this model has been proven to foster independent learning, a sense of responsibility, and the ability of students to integrate theoretical knowledge into the context of real-world problem solving.